Quality Risk Evaluation of the Whole Process of Assembly Building Based on Game Theory-Combinatorial Empowerment and Three-Dimensional Cloud Modeling - Qiao Sun; Ziyang Ye; Xin Wei; Zecheng Wang; Dongwei Li (Applied Sciences)
In the context of intelligent construction and building industrialization, assembly buildings face many challenges in quality management due to their special design and construction characteristics. Therefore, a comprehensive method for evaluating the quality risk of the whole process of assembly building is proposed. This method is based on game-theoretic combinatorial empowerment and three-dimensional cloud modeling. By identifying the key risk factors, analyzing and classifying the quality risks that may exist in the whole process of the assembly building project, using the game theory combination assignment method to determine its comprehensive weight, establishing the game-theoretic-combinatorial-assignment three-dimensional cloud model, calculating and comparing the distance between the evaluation cloud and the standard cloud, and determining the risk level of the indexes, thereby realizing the comprehensive assessment of the quality risk. Example validation shows that the method yields a risk level of II for the whole project, which is more consistent with the actual situation, and by comparing with the two-dimensional cloud model, it further verifies the effectiveness and advantages of the three-dimensional cloud model in identifying the high hidden risks, and provides a new idea and method for the quality management of the whole process of the assembled building.